Targeted IFNγ induction by a genetically engineered Salmonella typhimurium is the key to the liver metastasis inhibition in a mouse model of pancreatic neuroendocrine tumor - Hua, Zhan; Wu, Shan; Zhang, Yulian; Wang, Xiuhong; Cui, Ju; Li, Yunxuan; Yang, Chengcheng; Zhai, Min; Deng, Bo; Yu, Bin; Huang, Jian-Dong; Wang, Zai; et al. (Frontiers in Medicine, 2023)
Background: Liver metastasis is one of the primary causes of death for the patients with pancreatic neuroendocrine tumors (PNETs). However, no curative therapy has been developed so far.: The anti-tumor efficacy of a genetically engineered tumor-targeting Salmonella typhimurium YB1 was evaluated on a non-functional INR1G9 liver metastasis model. Differential inflammatory factors were screened by Cytometric Bead Array. Antibody depletion assay and liver-targeted AAV2/8 expression vector were used for functional evaluation of the differential inflammatory factors. Results: We demonstrated that YB1 showed significant anti-tumor efficacy as a monotherapy. SinceYB1 cannot infect INR1G9 cells, its anti-tumor effect was possibly due to the modulation of the tumor immune microenvironment. Two inflammatory factors IFNγ and CCL2 were elevated in the liver after YB1 administration, but only IFNγ was found to be responsible for the anti-tumor effect. Liver-targeted expression of IFNγ caused the activation of macrophages and NK cells, and reproduced the therapeutic effect of YB1 on liver metastasis. Conclusions: We demonstrated that YB1 may exhibit anti-tumor effect mainly based on IFNγ induction. Targeted IFNγ therapy can replace YB1 for treating liver metastasis of PNETs.The antitumor effect of IFNγ has been identified for a long time, but the therapeutic effects are controversial when using systemic injection. We demonstrated that livertargeted delivery of IFNγ by AAV2/8 vector could phenocopy the anti-liver metastases effect of an engineered Salmonella strain YB1 in a mouse model of pancreatic neuroendocrine tumor. The mechanism is not related to the adaptive immune regulation but may through the direct anti-tumor effect of IFNγ and the activated NK cells and macrophages. Our study demonstrates that targeted IFNγ therapy may have the potential application value in the treatment of certain types of tumors. The results based on our mouse model support further analysis of human tumor materials in the future.